Kepemimpinan Pengetua Mengikut Gender dan Tahap Motivasi Guru Sekolah Menengah di Daerah Kota Setar, Kedah Darul Aman - Nordin, Wan Daud (2004)

(untitled)
The purpose of this research is to see the relationship between the principal leadership by gender and the teacher's motivation at eight secondary school in Kota Star area, Kedah Darul Aman. The dimension of leadership style observe are the work structure and considerate. The research also see the difference in teacher's motivation base on the principal leadership style. The research also aim in determine whether the difference between the teacher's motivation base on demographic characteristic (sex, category of service and teaching experience) occurs. Instrument The Leader Behavior Description Questionnaire (LBDQ) build by Halpin (1966) and modified by researcher are use in measuring principal leadership style. Where else instrument A Questionnaire Measure of Individual Differences in Achieving Tendency (QMAT) build by Mehrabian and Bank (1978) are use in measuring teacher's motivation. Respondent for this research are the teachers from eight school in Kota Star area, Kedah Darul Aman. The number of research population sample are about 240 teachers from the school concern. Respondent involve in this research are 30 teachers from every school that are observe and are choose at random. Pioneer research are done at Simpang Kuala National Secondary School , Alor Star, Kedah Darul Aman (Men Principal) and Darul Aman National Secondary School, Alor Star, Kedah Darul Aman (Women Principal). In general, the output of the research found that it occurs a relationship between the principal leadership style by gender and the teacher's motivation at eight school in Kota Star area, Kedah Darul Aman.